2006
DOI: 10.1097/01.prs.0000185611.87601.b8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Total and Perfused Blood Vessels in Murine Skin Autografts Using a Fluorescent Double-Labeling Technique

Abstract: The short time course of vessel filling indicates that the initial onset of revascularization is attributable to early anastomoses between graft and bed vessels, mainly in the central area of the graft. These findings have implications for both autograft revascularization in a clinical setting and in the development of tissue-engineered skin substitutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…Reperfusion appeared to occur in an all-or-none pattern consistent with the mechanism of donor vascular network reconnection to recipient vessels. Though this has not been previously studied in orthotopic tracheal grafts, other studies have demonstrated similar mechanics of revascularization as well as time course in avascular grafts such as skin autografts (19,20) and peripheral nerve allografts (21). Interestingly, the transgenic Tie2/β-galactosidase recipients had many cells in the allograft expressing β-galactosidase.…”
Section: Figurementioning
confidence: 88%
“…Reperfusion appeared to occur in an all-or-none pattern consistent with the mechanism of donor vascular network reconnection to recipient vessels. Though this has not been previously studied in orthotopic tracheal grafts, other studies have demonstrated similar mechanics of revascularization as well as time course in avascular grafts such as skin autografts (19,20) and peripheral nerve allografts (21). Interestingly, the transgenic Tie2/β-galactosidase recipients had many cells in the allograft expressing β-galactosidase.…”
Section: Figurementioning
confidence: 88%
“…Early revascularization is attributable to newly formed vascular anastomoses between graft and recipient wound bed vessels; this occurs mainly in the central portion of the recipient bed and graft [32]. It would also be important to distinguish the participation of preexisting versus newly formed vessels in this model.…”
Section: Discussionmentioning
confidence: 98%
“…1C; 7.4 ± 2.5 vessels/cm 2 vs. 2.3 ± 0.8 vessels/cm 2 ; n = 12; P \ 0.001). It is important to note that full-thickness skin grafts revascularize primarily from the graft edges, unlike split-thickness grafts, which have been shown to revascularize not only from the graft edges but also from the underlying recipient wound bed [8,32]. Also, the hypodermal/adipose dermis/fascial fat layer (adipose dermis) and panniculus carnosus were all removed from the donor skin graft prior to transplantation.…”
Section: Eswt Enhances Ischemic Tissue Angiogenesis and Revascularizamentioning
confidence: 99%
“…10 In contrast, previous studies suggested that graft vessels may degenerate after reperfusion, leaving the basement membrane as a potential conduit for further vessel ingrowth. [11][12][13] Therefore, it was the aim of this study to gain further insight into the morphology and development of the vascular structures within the skin graft after reperfusion and to three-dimensionally visualize its capillary network.…”
mentioning
confidence: 99%